#TITLE_ALTERNATIVE# - Setiadi , Hendrawan
As apart of URGE Batch III research with object is Study on the Transport Distribution of Contaminated Sediment in Semarang Coastal Waters, study of pollutant spreading pattern in Semarang coastal waters was conducted by using field study and mathematical model. The analysis result of the water quality in 19 sampling stations indicated the existence of 4 species of heavy metal, i.e. Cadmium (Cd), Lead (Pb), Zinc (Zn), and Silver (Ag). The concentration pattern of each species presented unclear distribution pattern with the concentration in the eastern side of study area that located at 3000 m from source was higher than the other part. In the east monsoon (dry season) heavy metal concentration between 0.072 - 0.136 ppm, 0.155 - 0.490 ppm, 0.062 - 0.095 ppm, 0.071 - 0.105 ppm respectively, and in the west monsoon (rainy season) concentration between 0.014 - 0.015 ppm, 0.031 - 0.041 ppm, 0.110 - 0.238 ppm, 0.008 - 0.009 ppm respectively. The result of mathematical model simulation of heavy metal spreading pattern at the west monsoon, during the rainy season (February 24 - March 11, 1998), quantitatively gave spreading pattern of Zn as measured in the field. Simulation result of Zn spreading after 10 days showed that concentration is lower with the increasing distance, at 600 m from source concentration is varied from 0,033 to 0,064 ppm, then it became higher in eastern side of study area, at 3000 m from source, concentration about 0,105 - 0,117 ppm.